The Influence of Net Profit and Operating Cash Flow on Share Prices in Food and Beverages Companies Listed on The Indonesia Stock Exchange For The 2019-2022 Period - Tuti Supatminingsih (International Journal of Education, Vocational and Social Science, 2024)
This research is intended to investigate the impact of net profit and operating cash flow on share prices in food and beverages companies listed on the Indonesia Stock Exchange during the 2019-2022 period. By utilizing financial data and share prices, regression methodology is applied to evaluate the relationship between the independent variables, namely net profit and operating cash flow, and the dependent variable, namely share prices. Research findings show that there is a significant influence between net income and share prices, while operating cash flow does not have a significant impact on share prices. Furthermore, net profit and share price simultaneously influence share prices.